Macroeconomic determinants of mutual funds performance in Ghana - Adjei Gyimafi Gyamfi; Bismark Addai; George Kwasi Asamoah (Cogent Economics & Finance, 2021)
This study examines the impact of key macroeconomic variables on mutual funds' financial performance in Ghana. We employ the Pooled Mean Group (PMG) estimation of the Autoregressive Distributed Lag (ARDL) model to analyze the macroeconomic determinants of mutual funds in Ghana for the period 2007-2016. The study documents homogenous long-run significant positive impacts of exchange rate, inflation, T-Bill, GDP growth on mutual funds' financial performance, and a homogeneous long-run negative significant impact of monetary policy rate on the financial performance of mutual funds. The study also establishes heterogeneous short-run respective significant negative and positive impacts of T-Bill and monetary policy on mutual fund's financial performance. Unlike many previous studies that used stock data to estimate mutual funds' performance, accounting data is used in this study. Second, we incorporate monetary policy rate in our study variables since most of the prior studies ignored that variable. Finally, the outcome of our study contributes to existing knowledge on the short-run and long-run effects of macroeconomic variables on the financial performance of mutual funds from the perspectives of a developing country.
Keywords: E44; G1; G2; 330; Autoregressive Distributed Lag (ARDL); financial performance; Macroeconomic; mutual fund; Pooled Mean Group (PMG)